Accumulation of damage and fracture of aluminium alloy grains - Корчук, О.Ю. (Proceedings of National Aviation University, 2005)
Results of the investigation of aluminum alloy AD-1 grains microhardness under fatigue and results of the fatigue crack monitoring are presented. The link of microhardness with kinetic characteristics of fracture process is determined. New approach for estimation of crystallographic orientation influence on fatigue life of single-crystal and crystallites is proposed.